Pengaruh Beban Kerja dan Faktor Lingkungan Fisik Terhadap Tekanan Darah, Denyut Nadi dan Tingkat Kelelahan Pekerja Bagian ARC FURNACE dan ROLLING MILL PT. Inti General Yaja Steel Semarang - Nurullita, Ulfa; Suhartono, Suhartono; Joko, Tri (Jurnal Kesehatan Lingkungan Indonesia, 2007)
ABSTRACT Background: The existence of work efficiency can be reached with balancing work capacity and increase capacity in the working environment. One factor  in the  working  environment that cause work  inefficiency  is physical factor namely  heat stress, noise and lighting. The influence of physical  factors are indicated by  physical performance of the worker’s blood pressure  and fatigue level. Objective: to find out  the influence of work capacity and physical factors in the working  environment on the blood pressure, pulse, fatigue level of worker in  Arc Furnacearea  and Rolling Mill section, PT Inti General Yaja Steel Semarang. Methode: Type of the research was quasy experimental  with one group pre and post test design. The population were 178 worker  and  47 workers were  taken in this research. Confounding factors was cigarettes, cafein, drug consumption, and nutrition status. Result: There was  found differences of blood pressure before working  and after working (systole; p- Wilcoxon Sign Ranks = 0,001, diatole; p- Wilcoxon Sign Ranks, = 0,003). The average before working (systole=119,7 mmHg, diastole= 84 mmHg) was higher than after working (systole=107,2 mmHg, diastole= 78,9 mmHg). There was  also  differences of  pulse rate before working  and after working  (p-paired t test= 0,001). The average of pulse before working (81,5 times/minute) was lower than after working (87,5 times/minute). There was found differences of fatigue level before working and after working (p- Wilcoxon Sign Ranks=0,001). The average of fatigue level before working was measured  253,2 millisecond lower than after working  (290,7 milisecond). Conclusion: There is found  differences  of blood pressure, pulse and fatigue level before working  and after working. There are no differences of blood pressure transition, pulse transition and fatigue transition  based on heat stress, noise, lighting, work capacity, cigarettes, cafein, drug consumption and nutrition status.   Keywords : work capacity, physical factor , working environment, blood pressure, fatigue level